KG Resource Pack Mathematics - Term I - THE CITY SCHOOL (PAKISTAN THE CITY SCHOOL)
This resource pack contains a comprehensive set of activities and exercises designed to develop mathematical skills in kindergarten students during Term I.
Includes activities and exercises for kindergarten mathematics
For kindergarten students
Keywords: Mathematics - Study and teaching (Kindergarten)-Early childhood education